Memorizing the Qur'an as Banjarese Bride-Price (A Study of Living Quran and Hadith) - Munirah Munirah (Universitas Islam Negeri Mataram, 2017)
One example of the living Qur’an and hadith are found in South Borneo. Living Qur’an and hadith refers to various ways in which this scriptures are practiced in Muslim daily live. In South Borneo, this deals with the phenomenon of memorizing the Qur’an as a bride-price (jujuran) for marriage among the Banjarese people. This tradition has been practiced for various reasons. Using phenomenological method, this study records the views of the people peforming this tradition and attempts to explain its practice and meaning. This study reveals that jujuran is an acculturation of the Qur’an with the local tradition. The people believe in the power of the Qur’an and make this to bless their important life cycle, such as marriage. The jujuran reflects various reasons, ranging from groom’s seriousness to memorize the Qur’an and to marry and the best award for brides. However, most do not know the authoritative tradition from the Prophet regarding the bride-price of memorizing the Qur’an but are inspired by popular literature and novel that contain stories of the Qur’an as bride-price.